Magico-religious and social belief of tribals of district Udaipur, Rajasthan - Vandana Singh Kushwah; Rashmi Sisodia; Chhaya Bhatnagar (BMC, 2017)
Abstract Background Religious beliefs and practices have long influenced human perceptions and uses of nature. Animals in particular play a prominent role in magico-religious practices and provide historical and cultural depth of these relationships. Understanding human-faunal relations is often fundamental to the cause of meaningful wildlife conservation. This study investigates the domestic and wild harvested species used for spiritual and religious purposes among the tribals of six tehsils of Udaipur district. Methods The ethnozoological data were obtained by an emic approach, applying different tools such as semi-structured interviews, participatory rural appraisal, key informant interviews, and focus group discussions. The scientific name and species of animals were identified using relevant and standard literature. Present investigation is a part of major concept worked out for study on tribal people and their beliefs. Ethnozoological information was collected by interview of 150 tribals. The questionnaire was prepared in Hindi keeping all parameters in mind. A total of 55 respondents (35 males and 20 females) answered to the magico-religious parameter. The collected data were analyzed through informant fidelity level (FL). Results The present study was undertaken to have an insight of the ethnozoological uses of animals prevalent in Bhil, Meena, and Kathodi tribes inhabiting the Udaipur district of Rajasthan. A total of 25 animals used for magico-religious and social purposes were recorded from the study area. Out of the total number of animals, 60% (15) were mammals, 24% (6) were birds, 12% (3) were reptiles, and the rest 4% (1) were the mollusks. Of the total ethnozoological practices, 64% fall in the magico-religious category, 12% in socio-cultural category, 12% in the category of ethnomusical, and 12% in the category of taboos. Conclusions The tribal people maintain strong ties with animals at both the material and spiritual level. Study reveals that traditional people depend on local therapies either magico-religious or natural ones in absence of awareness, modern medical facilities, expensive drugs, and poor transportation. However, the use of animal material in such practices is on a decline.